First insights into the living groundwater mycobiome of the terrestrial biogeosphere. (15th November 2018) - Nawaz, Ali; Purahong, Witoon; Lehmann, Robert; Herrmann, Martina; Totsche, Kai Uwe; Küsel, Kirsten; Wubet, Tesfaye; Buscot, François
Abstract: Although fungi play important roles in biogeochemical cycling in aquatic ecosystems and have received a great deal of attention, much remains unknown about the living fractions of fungal communities in aquifers of the terrestrial subsurface in terms of diversity, community dynamics, functional roles, the impact of environmental factors and presence of fungal pathogens. Here we address this gap in knowledge by using RNA-based high throughput pair-end illumina sequencing analysis of fungal internal transcribed spacer (ITS) gene markers, to target the living fractions of groundwater fungal communities from fractured alternating carbonate-/siliciclastic-rock aquifers of the Hainich Critical Zone Exploratory. The probed levels of the hillslope multi-storey aquifer system differ primarily in their oxygen and nitrogen content due to their different connections to the surface. We discovered highly diverse living fungal communities (384 Operational Taxonomic Units, OTUs) with different taxonomic affiliations and ecological functions. The observed fungal communities primarily belonged to three phyla: Ascomycota, Basidiomycota and Chytridiomycota. Perceived dynamics in the composition of living fungal communities were significantly shaped by the concentration of ammonium in the moderately agriculturally impacted aquifer system. Apart from fungal saprotrophs, we also detected living plant and animal pathogens for the first time in this aquifer system. This work also demonstrates that the RNA-based high throughput pair-end illumina sequencing method can be used in future for water quality monitoring in terms of living fungal load and subsequent risk assessments. In general, this study contributes towards the growing knowledge of aquatic fungi in terrestrial subsurface biogeosphere. Highlights: First RNA-based study using Illumina platform studying fungi in the aquifer system. A diverse pool of living aquatic fungal species detected in subsurface aquifers. NH4 + and TIC supply correlate with the living fungal community composition in the aquifers. Saprotrophs along with animal and plant pathogens were most frequently detected living functional groups.